Susceptibility of Healthcare Professionals to Vaccine-Preventable Diseases: Critical Care Unit, Hospital de Clínicas, San Lorenzo-Paraguay 2021 - Silva Estigarribia, Arturo Yvan; Rodríguez-Riveros, María Isabel (Medicina Clínica y Social, 2025)
Introduction:  Vaccination is a key strategy to prevent communicable diseases and reduce occupational risks among healthcare workers. In critical care units, it ensures not only individual protection but also patient safety. Objective: To determine susceptibility to vaccine-preventable diseases among healthcare professionals in the Critical Care Unit of Hospital de Clínicas, San Lorenzo, Paraguay, 2021. Methodology: An observational, descriptive, cross-sectional, quantitative study was conducted with a non-probabilistic sample of 90 professionals. Data were collected using a validated questionnaire and analyzed with EpiInfo 7.2. Susceptibility was assessed based on knowledge, vaccination coverage, institutional factors, and use of personal protective equipment. Results: Most participants were female (68%), aged 31–40 years (57%), and nurses (80%). A total of 97% correctly identified hepatitis B as viral in origin, but only 60% had a complete vaccination scheme. Regarding influenza, 99% recognized the annual schedule and 80% were immunized. Tdpa coverage reached 78%, while 97% had received the COVID-19 vaccine. Overall, 73% complied with the recommended vaccination scheme for healthcare workers. Institutionally, 96% reported that the hospital managed and required vaccination; 77% acknowledged provision of masks and 71% of gloves. In terms of susceptibility, 68% showed low risk as they had five or more complete vaccines. Conclusions: Healthcare workers showed high coverage and low susceptibility, though gaps remain in incomplete schemes and vaccination record availability. Strengthening institutional policies is recommended to ensure complete and updated immunization for all professionals
Keywords: Vaccine; Healthcare professional; Susceptibility